Adverse Childhood Experiences and Insufficient Sleep Among U.S. Children and Adolescents. - Lin, Susan X.; Cheslack-Postava, Keely; McReynolds, Larkin; Amsel, Lawrence; Bresnahan, Michaeline; Hoven, Christina W. (Academic Pediatrics, 2022)
objective: To examine associations between adverse childhood experiences (ACEs) and age-specific insufficient sleep duration (ISD) in American youth. Methods: Data from the 2016-2017 National Survey of Children's Health, a sample of 46,209 youth ages 6 to 17 were analyzed. The main outcome was sleep duration that did not meet the recent recommendations of the American Academy of Sleep Medicine. Nine types of ACEs. as well as a cumulative count of ACEs, were examined as independent variables in unadjusted and adjusted logistic regression models. Results: Approximately half of U.S. children and adolescents (ages 6-17) experienced at least one ACE and a third did not get sufficient sleep. Among those exposed to any ACE. 40.3% had ISD. Seven of the 9 ACEs examined were significantly associated with a 20% to 60% increase in odds of not getting sufficient sleep (adjusted ORs between 1.2 and 1.6). Children exposed to 2 or more ACEs were nearly twice as likely as those exposed to no ACE to have ISD (adjusted OR = 1.7, 95% CI: 1.5-1.9). Moreover, each individual ACE, except parental death was significantly associated with more than 1 hour less sleep than recommended. Conclusions: This study reports the association of specific and cumulative ACEs with ISD in a nationally representative sample of American youth. The study findings underscore the importance of screening for both ACEs and insufficient sleep during primary care encounters and addressing potential sleep problems in those exposed to ACEs.